2021
DOI: 10.3390/healthcare9050602
|View full text |Cite
|
Sign up to set email alerts
|

Factors beyond Workplace Matter: The Effect of Family Support and Religious Attendance on Sustaining Well-Being of High-Technology Employees

Abstract: Background: Apart from the workplace, drawing support from family and religion is critical to maintaining the well-being of high-technology employees. Relying on the job demands-resources model and the positive affective spillover effect, the aim of this study was to investigate the mediated relationship of family support, work engagement and subjective well-being, and the moderating effect of religious attendance on the mediated relationship. Methods: A cross-sectional research design was adopted. Mediation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…The study demonstrates a need to accommodate religion in the organisation; this could foster ethical business conduct and interest in CSR practices, as decision‐makers have to be evaluated based on their intentions to contribute to society rather than to financial results alone. Additionally, enhanced integration of religion into the organisation may lead to improvements in employee motivation and productivity (Syarifuddin et al, 2021), employee well‐being (Huang et al, 2021) and greater attraction of local talent, all of which can have a positive effect on organisational performance. Moreover, the importance of the identified specific Islamic principles suggests that foreign organisations interested in operating in the examined countries may want to consider CSR forms divergent from their domestic market.…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrates a need to accommodate religion in the organisation; this could foster ethical business conduct and interest in CSR practices, as decision‐makers have to be evaluated based on their intentions to contribute to society rather than to financial results alone. Additionally, enhanced integration of religion into the organisation may lead to improvements in employee motivation and productivity (Syarifuddin et al, 2021), employee well‐being (Huang et al, 2021) and greater attraction of local talent, all of which can have a positive effect on organisational performance. Moreover, the importance of the identified specific Islamic principles suggests that foreign organisations interested in operating in the examined countries may want to consider CSR forms divergent from their domestic market.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study focuses on dentists, it is essential to recognize the possible impact of the pandemic on all other professionals who perform functions in the dental environment, such as oral health technicians and assistants. One study reported that only 27% of U.S. dentists were able to offer full pay to their employees [27].…”
Section: Discussionmentioning
confidence: 99%